Bloodshot : Rising Spirit - Nadler, Lonnie; Thompson, Zac; Grevioux, Kevin; Rahal, Eliot; Lashley, Ken; Morales, Rags (Valiant, 2021)
Teoksen sarjakuvat julkaistu alunperin 2018-2019.
Keywords: supersankarit